Corotating interaction regions (CIRs) at sub-harmonic solar rotational periods and their impact on ionosphere-thermosphere system during the extreme low solar activity year 2008 - Tulasiram, S.; Yamamoto, M.; Veenadhari, B.; Kumar, Sandeep; Gurubaran, S. (My University, 2012)
The past solar minimum year 2008 has been exceptionally quiet with more than 70% spotless days and the solar EUV irradiance and F10.7 solar flux levels steadily at low values for a prolonged period. During this unique solar minimum epoch, however, the geospace environment is recurrently intercepted by solar wind high speed streams from the low-latitude coronal holes, which are the primary contributors for recurrent geomagnetic activity at solar rotational (27-day) and its sub-harmonic (13.5 and 9-day) periodicities. In response, both the neutral and ionized upper atmospheric properties continued to ring with same periodicities. The results indicate that both the neutral and electron density response at 400 km (topside ionosphere) is dominated by the changes in temperature and/or scale height and exhibits coherent enhancements concurrently with the periodicities in geomagnetic activity. However, the equatorial electrojet (EEJ) strength does not exhibit any recurrent signatures at these periodicities.
Keywords: Corotating interaction regions (CIRs); Equatorial electrojet (EEJ) strength; Solar rotational periodicity; Solar wind parameters; Geomagnetic activity indexes; Electron density; Neutral density